2016
DOI: 10.7554/elife.13149
|View full text |Cite
|
Sign up to set email alerts
|

Internalization and presentation of myelin antigens by the brain endothelium guides antigen-specific T cell migration

Abstract: Trafficking of myelin-reactive CD4+ T-cells across the brain endothelium, an essential step in the pathogenesis of multiple sclerosis (MS), is suggested to be an antigen-specific process, yet which cells provide this signal is unknown. Here we provide direct evidence that under inflammatory conditions, brain endothelial cells (BECs) stimulate the migration of myelin-reactive CD4+ T-cells by acting as non-professional antigen presenting cells through the processing and presentation of myelin-derived antigens in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 33 publications
2
34
1
Order By: Relevance
“…33 The internalization and presentation of myelin antigens by the brain endothelial cells through MHC class II guide the migration of antigen-specific T cells into the CNS. 34 The findings of this study suggest that IFN-γ-induced MHC molecules, PD-L1, ICAM-1 and VCAM-1, on endothelial cells may also help in the selective transmigration of neuronal antigen-specific effector T cells during inflammation and autoimmunity ( Figure 5). Collectively, all these mechanisms may have a cumulative effect and consequently play a decisive role in increased severity of EAE in IFN-γ − / − or IFN-γR − / − mice.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…33 The internalization and presentation of myelin antigens by the brain endothelial cells through MHC class II guide the migration of antigen-specific T cells into the CNS. 34 The findings of this study suggest that IFN-γ-induced MHC molecules, PD-L1, ICAM-1 and VCAM-1, on endothelial cells may also help in the selective transmigration of neuronal antigen-specific effector T cells during inflammation and autoimmunity ( Figure 5). Collectively, all these mechanisms may have a cumulative effect and consequently play a decisive role in increased severity of EAE in IFN-γ − / − or IFN-γR − / − mice.…”
Section: Discussionmentioning
confidence: 75%
“…(viii) IFN‐γ is known to upregulate PD‐1 on effector CD4 + T cells, and PD‐L1 on antigen‐presenting cells during EAE 33 . The internalization and presentation of myelin antigens by the brain endothelial cells through MHC class II guide the migration of antigen‐specific T cells into the CNS 34 . The findings of this study suggest that IFN‐γ‐induced MHC molecules, PD‐L1, ICAM‐1 and VCAM‐1, on endothelial cells may also help in the selective transmigration of neuronal antigen‐specific effector T cells during inflammation and autoimmunity (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…These contacts induce the effector T cells to produce pro-inflammatory mediators, trigger tissue invasion and promote the formation of inflammatory infiltrates (57). Other reports confirm that T cells become activated in the perivascular space, but not within the vascular lumen, although previous in vitro studies have shown that endothelial cells can present antigen to adherent myelin-specific T cells (107, 109). In a MBP transfer EAE rat model, the comparison of highly immunogenic MBP-specific and modestly immunogenic MOG-specific T cells revealed that regardless of antigen specificity, the two cell types crawled with similar velocities in blood vessels (107).…”
Section: The Dynamics Of T Cell Activation In the Spinal Cord During Eaementioning
confidence: 86%
“…The endothelium is involved in MS pathology by recruitment of immune cells to the CNS (Yun, Minagar, & Alexander, 2017). Endothelial cells are involved in antigen presentation of CNS components to antigen-specific lymphocytes (Galea et al, 2007;Lopes Pinheiro et al, 2016;Traugott & Raine, 1985). Blocking co-inhibitory molecules PD-L1 or PD-L2 on human endothelial cells facilitates transmigration responses of lymphocytes in vitro (Pittet, Newcombe, Prat, & Arbour, 2011;Rodig et al, 2003).…”
Section: Discussionmentioning
confidence: 99%